Verbal transfigurations: when the daughters of the night dance in daylight - Schilo, Ann (the Australian Council of University Art & Design Schools (ACUADS), 2009)
With the rise of creative doctorates in art schools in Australia there has been a concomitant concern over the relationship between theory and practice, between creative work and exegesis. Since the symposium Illuminating the Exegesis at the University of Ballarat in 2003, the majority of institutions have formulated their understandings of what constitutes an exegesis and established guidelines for their research students. Yet for many art students there still remains an uncomfortable relationship between what they do in the studio and the written word. This paper seeks an understanding of the various dimensions of theory since the development of creative doctorates. Through anecdotal study of the perceptions of students, it focuses upon the practice of exegetical writing, examining ways and means by which students negotiate their word phobias to articulate their ideas. It explores how writing can move them outside their comfort zones and cause them to reflect upon art, its histories, theories and practices. By transfiguring their ideas, those daughters of the night (that) have to be educated, presented (Clement 1994, p34) nascent writers can eventually find voice.